MULTIMEDIA-ASSISTED GENRATIVE LEARNING MODEL TOWARDS IPA LEARNING SATISFACTION IN STUDENTS OF GRADE IV ELEMENTARY SCHOOL ACHIEVEMENT SCHOOL YEAR 2020/2021 (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The development of science and technology has brought about changes in almost all aspects of human life. In addition to bringing benefits to human life, on the one hand these changes also lead us to an era of increasingly fierce global competition. The Generative learning model is one of the learning models that make IPA learning more meaningful and can create a constructivist learning climate with the basic assumption that knowledge is built into students' minds. This research aims to find out the influence of multimedia-assisted generative learning models on IPA learning satisfaction in grade IV students in Elementary School Achievement School. In the Generative learning model, students themselves are more mentally active in building their knowledge, while teachers are more instrumental as facilitators and mediators in learning. The type of research conducted is quantitative pseudo-experiments and the design of non-equivalent control group design. In this design there are experimental samples and control samples. The samples used were two 4th grade groups of Insan Achievement School Elementary School. After research conducted in grade IV elementary school achievement school obtained results, namely the difference in average questionnaire level of IPA learning satisfaction between groups of students who were taught using multimedia-assisted generative learning model with conventionally taught students. This is obtained from the comparison of mean after being given the questionnaire of both groups. The experimental group had a mean of 119.79 higher than the control group's mean value of 96,429 ANAVA test results and the learning satisfaction questionnaire of Fhi numera = 21,348 then compared to Ftable = 4.03, so Fcalculated > Ftable. There is a rejection of H0. So it can be concluded that the Multimedia Assisted Generative Learning Model has a significant effect on IPA learning satisfaction in students of grade IV Elementary School Achievement School Year 2020/2021.